Proceedings of the International Conference on Data Engineering and Communication Technology ICDECT 2016, Volume 1 - Satapathy, Suresh Chandra; Bhateja, Vikrant; Joshi, Amit.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This two-volume book contains research work presented at the First International Conference on Data Engineering and Communication Technology (ICDECT) held during March 10-11, 2016 at Lavasa, Pune, Maharashtra, India. The book discusses recent research technologies and applications in the field of Computer Science, Electrical and Electronics Engineering. The aim of the Proceedings is to provide cutting-edge developments taking place in the field data engineering and communication technologies which will assist the researchers and practitioners from both academia as well as industry to advance their field of study.
Chapter 1. Singular Value Decomposition and Discrete Wavelet Transform Based Fingerprint Gender Classification -- Chapter 2. Isolated Word Speech Recognition System Using Deep Neural Networks -- Chapter 3. A Proposed Resource Sharing Architecture for Multitenant SaaS Applications -- Chapter 4. Privacy Preserving Profile Matching System for Trust-Aware Personalized User Recommendations in Social Networks -- Chapter 5. Performance Analysis of Single Phase Bi-Directional Converter for Power Factor Correction and Voltage Stabilization -- Chapter 6. Ensemble Method Using Correlation Based Feature Selection with Stratified Sampling for Classification -- Chapter 7. Suffix Array Blocking for Efficient Record Linkage and De-duplication in Sliding Window Fashion -- Chapter 8. Robust Dynamic Sliding Mode Control for a Class of Uncertain Multi-variable Process -- Chapter 9. Fault Tolerance Communication in Mobile Distributed Networks -- Chapter10. Analysis of Bathymetry Data for Shape Prediction of a Reservoir -- Chapter 11. An Extensive Survey on Diagnosis of Diabetes Mellitus in Healthcare -- Chapter 12. Convolution Encoder for BER Analysis Using Doppler Frequency Shift in the Packet Erasure Network -- Chapter 13. Study of Variation in Ambient Noise with Fluctuations of Surface Parameters for the Indian Ocean Region -- Chapter 14. ANIDS: Anomaly Network Intrusion Detection System Using Hierarchical Clustering Technique -- Chapter 15. Semantic-Based Service Recommendation Method on Map-Reduce Using User Generated Feedback -- Chapter 16. Implementation of DSTC and PSO Algorithm Using CLD to Improve the Performance of MANET -- Chapter 17. Progressive Review towards Deep Learning Techniques -- Chapter 18. Design & Simulation of Two Stage Operational Amplifier with Miller Compensation in Nano Regime -- Chapter 19. Mobile Apps Classification with Risk Score by Exploiting the Enriched Information of App Context -- Chapter 20. Ultra-Wideband Differential Fed Antenna with Improved Radiation Pattern -- Chapter 21. An Automatic Approach to Segment Retinal Blood Vessels and Its Separation into Arteries/Veins -- Chapter 22. Design of Microstrip Antenna with Improved Bandwidth for Biomedical Application -- Chapter 23. Extended ExOR Opportunistic Routing Algorithm Based on Broadcasting -- Chapter 24. Factors Influencing Group Member Satisfaction in the Software Industry -- Chapter 25. PI-PD Smith Predictor Based Cascade Controller Designing -- Chapter 26. Speech Enhancement Using Transform Domain Techniques -- Chapter 27. Indian Election Using Twitter -- Chapter 28. Adaptive Data Transmission in WSN Using Enhanced Path Assured Transmission Protocol -- Chapter 29. Cohort Intelligence and Genetic Algorithm along with Modified Analytical Hierarchy Process to Recommend an Ice-cream to Diabetic Patient -- Chapter 30. Theoretical Framework for Privacy in Interpersonal Information Communication -- Chapter 31. Gist, HOG and DWT Based Content Based Image Retrieval for Facial Images -- Chapter 32. Low Cost Intelligent Irrigation System -- Chapter 33. IVIFS and Decision Making -- Chapter 34. Comparative Analysis of Integer and Fractional Order Controller for Time Delay System -- Chapter 35. A Secure Authentication Scheme in Multi-Operator Domain (SAMD) for Wireless Mesh Network -- Chapter 36. A Wireless Sound Alert and Person Identity Notification System for People with Hearing Disabilities -- Chapter 37. Automatic Language Identification and Content Separation from Indian Multilingual Documents Using Unicode Transformation Format -- Chapter 38. Constrained Power Loss Minimization of DC Micro Grid Using Particle Swarm Optimization -- Chapter 39. Selective Cropper for Geometrical Objects in Openflipper -- Chapter 40. OpinionMining Feature Extraction Using Domain Relevance -- Chapter 41. Imaging Based Method for Precursors of Impending Disease from Blood Traces -- Chapter 42. A Hybrid of DEA-MLP Model for Stock Market Forecasting -- Chapter 43. Low Noise Tunable Band-Pass Filter for ISM 2.4 GHz Bluetooth Transceiver in ±0.7V 32nm CNFET Technology -- Chapter 44. Classification of Punjabi Folk Musical Instruments Based on Acoustic Features -- Chapter 45. Combined DWT-DCT Based Video Watermarking Algorithm Using Arnold Transform Technique -- Chapter 46. A Basic Simulation of ACO Algorithm Under Cloud Computing for Fault Tolerant -- Chapter 47. A Neuromorphic Majority Function Circuit with O(n) Area Complexity in 180nm CMOS -- Chapter 48. Human Action Recognition: An Overview -- Chapter 49. Performance Analysis of CREIDO Enhanced Chord Overlay Protocol for Wireless Sensor Networks -- Chapter 50. Implementation of Hashing in Virtual Tour -- Chapter 51. RENT: Regular Expression and NLP based Term Extraction Scheme for Agricultural Domain -- Chapter 52. Review of Clustering Techniques -- Chapter 53. Novel Zero Voltage Transition Based Interleaved Boost Converter -- Chapter 54. A Survey of Cloud Based Healthcare Monitoring System for Hospital Management -- Chapter 55. Design of Common Sub Expression Elimination Algorithm for Cyclotomic Fast Fourier Transform over GF (23) -- Chapter 56. On Analysis of Wheat Leaf Infection By Using Image Processing -- Chapter 57. Divisive Hierarchical Bisecting Min Max Clustering Algorithm -- Chapter 58. Open Source Big Data Analytics Technique -- Chapter 59. Security Analysis of Online Cab Booking Android Application -- Chapter 60. Analyzing Security Schemes in Delay Tolerant Networks -- Chapter 61. An Approach to Design an IoT Service for Business-Domain Specific Web Search -- Chapter 62. Weather Forecasting Using ANN with Error Back Propagation Algorithm -- Chapter 63. Coherent Rule Mining Using AIR -- Chapter 64. Enhanced Data Dissemination in a Mobile Environment -- Chapter 65. Adaptive Ontology Construction Method for Crop Pest Management -- Chapter 66. Deployment of Data Aggregation Technique in Wireless Sensor Network -- Chapter 67. Energy Efficient Self-Organization Wireless Sensor Network for Traffic Management in Smart Cities -- Chapter 68. Inter Area Frequency Monitoring in a Large Power Grid Network -- Chapter 69. Detection of Rogue Access Point Using Various Parameters -- Chapter 70. A Survey on Wireless Security: IP Security Concern -- Chapter 71. An Enhanced Framework to Design Intelligent Course Advisory Systems Using Learning Analytics -- Chapter 72. Player Tracking in Sports Video Using Optical Flow Analysis -- Chapter 73. Integrating Hybrid FMEA Methodology with Path Planning Decisions in Autonomous Vehicles -- Chapter 74. An Evaluative Model for Discriminative Dictionary Learning with Hybrid Local binary Patterns Based Feature Extraction for Bone Age Assessment in Content Based Image Retrieval -- Chapter 75. Evaluation of Prioritized Splay Tree Rotation Algorithm for Web Page Re-Organization -- Chapter 76. A Prototype Model for Deriving Social Media Intelligence Using Opinion Mining from Microblog Data -- Chapter 77. Implementation for Securing the Cloud Data and Providing Secured Access Across the Network -- Chapter 78. Integration of Mel-frequency Cepstral Coefficients with Log Energy and Temporal Derivatives for Text-independent Speaker Identification -- Chapter 79. Traffic Violation Detection and Penalty Generation System at a Street Intersection -- Chapter 80. Novel Speech Processing Algorithm for Perception Improvement & Needed Research for Hearing Impaired.
Keywords: Computational intelligence; Telecommunication; Artificial intelligence; Data protection; Computational Intelligence; Communications Engineering, Networks; Artificial Intelligence; Data and Information Security